2008
DOI: 10.1021/jp8092429
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hollow Gallium Nitride Spheres via Silica Sphere Templates

Abstract: We report the formation of hollow GaN spheres using silica sphere templates. First, silica spheres with an average diameter of ∼130 nm were synthesized. A mixture of GaCl 3 , silica spheres, water, and urea in 2-propanol was prepared and heated to 100°C for 24 h to generate silica spheres with γ-Ga 2 O 3 nanoparticle shells. Decomposition of urea and its reaction with water slowly increased the solution pH to ∼8; this controlled reaction is the key to forming uniform γ-Ga 2 O 3 shells with a thickness of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Various methods have been developed for preparing silicate materials with hollow structure. The common route for preparing hollow microspheres is to coat nanocrystals on the surfaces of templates followed by removing the templates through etching or calcinations [13][14][15]. For example, nickelsilica and copper-silicate composite hollow microspheres have been synthesized through such method [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been developed for preparing silicate materials with hollow structure. The common route for preparing hollow microspheres is to coat nanocrystals on the surfaces of templates followed by removing the templates through etching or calcinations [13][14][15]. For example, nickelsilica and copper-silicate composite hollow microspheres have been synthesized through such method [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to crystal defects from the aggregations composed of small AlN particles. 20 As studied previously, 5,21 vacancies and certain oxygen-related impurities were common defects in AlN nanostructures. However, a value of 3.9 eV for AlN:0.5%Tb is obtained.…”
Section: Photocatalytic H 2 Evolution Activitymentioning
confidence: 66%
“…For instance, These reports involve removing the core by calcinations 21,32 or dissolution into solvents. 31,33 Recently, wu et al reported a facile approach to prepare monodisperse hollow silica or titania spheres via a one-step process. [34][35][36] In that method, aqueous ammoniacal alcohol was used as the catalyst and medium.…”
Section: Sol-gelmentioning
confidence: 99%